The moderate size 2019 September Mw 5.8 Silivri earthquake unveils the complexity of the Main Marmara Fault shear zone - Karabulut, Hayrullah; Guvercin, Sezim Ezgi; Eskikoy, Figen; Konca, Ali Ozgun; Ergintav, Semih (OXFORD UNIV PRESS, 2021)
The unbroken section of the North Anatolian Fault beneath the Sea of Marmara is a major source of seismic hazard for the city of. Istanbul. The northern and currently the most active branch, the Main Marmara Fault (MMF), is segmented within a shear zone and exhibits both partially creeping and locked behaviour along its 150 km length. In 2019 September, a seismic activity initiated near MMF, off-coast the town of Silivri, generating 14 earthquakes >= M-w 3.5 in a week. The M-w 5.8 Silivri earthquake, is the largest in the Marmara Sea since the 1963 M-w 6.3 Cmarcik earthquake. Our analyses reveal that the activity started in a narrow zone (similar to 100 m) and spread to similar to 7 km following an M-w 4.7 foreshock within similar to 2 d. The distribution of relocated aftershocks and the focal mechanisms computed from regional waveforms reveal that the M-w 5.8 earthquake did not occur on the MMF, but it ruptured similar to 60 degrees north-dipping oblique strike-slip fault with significant thrust component located on the north of the MMF. Finite-fault slip model of the main shock shows 8 km long rupture with directivity toward east, where the ruptured fault merges to the MMF. The narrow depth range of the slip distribution (10-13 km) and the aftershock zone imply that the causative fault is below the deep sedimentary cover of the Marmara Basin. The distribution of aftershocks of the M-w 5.8 event is consistent with Coulomb stress increase. The stress changes along MMF include zones of both stress decrease due to clamping and right-lateral slip, and stress increase due to loading.
Keywords: Earthquake source observations; Seismicity and tectonics; Transform faults; INVERSION; SEA; CONSTRAINTS; SEISMICITY; NUCLEATION; EVOLUTION; RUPTURE; BASIN; Geochemistry & Geophysics